Motivation and Benefits of Implementation and Certification according ISO 9001 – the Portuguese Experience - Santos, Gilberto (2014)
The aim of the research is to analyze the different aspects associated with the motivation and benefits of certified ISO 9001 companies in Portugal. A total of 426 certified Portuguese companies were surveyed. The response rate was equal to 61.03 percent. Our results suggest that the main motivation for certification were “improvement of quality”, “improvement of company image”, “marketing advantage”, “give empowerment to workers / capturing workers knowledge” and “cost reduction”. The main benefits that Portuguese companies have gained from the referred certification have been, among others, the improvement of “procedures”, beneficial effect on the “company’s image”, the improvement of quality products/services, increase of the “customer satisfaction”, improvement of “on-time delivery”; improvement the “morale” of workers’ increase in productivity and decrease of “production costs”, among others. The surveyed firms belong only to the Minho region of the north of Portugal. This paper aims to provide a contribution to the research related to the motivation and benefits associated to the quality management systems. The selection of the motives and benefits were validated through statistical analysis and the relationship between expected and perceived benefits was discussed.